Influence of beta-cyclodextrin on the properties of norfloxacin form A - Chierentin, Lucas [UNESP]; Garnero, Claudia; Chattah, Ana Karina; Delvadia, Poonam; Karnes, Thomas; Longhi, Marcela Raquel; Salgado, Herida Regina Nunes [UNESP] (Springer, 2015)
Cyclodextrins are able to form host-guest complexes with hydrophobic molecules to result in the formation of inclusion complexes. The complex formation between norfloxacin form A and beta-cyclodextrin was studied by exploring its structure affinity relationship in an aqueous solution and in the solid state. Kneading, freeze-drying, and physical mixture methods were employed to prepare solid complexes of norfloxacin and beta-cyclodextrin. The solubility of norfloxacin significantly increased upon complexation with beta-cyclodextrin as demonstrated by a solubility isotherm of the AL type along with the results of an intrinsic dissolution study. The complexes were also characterized in the solid stated by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), Fourier-transform infrared (FT-IR) spectroscopy, X-ray diffractometry, scanning electron microscopy (SEM), and solid-state nuclear magnetic resonance (ssNMR) spectrometry. The thermal analysis showed that the thermal stability of the drug is enhanced in the presence of beta-cyclodextrin. Finally, the microbiological studies showed that the complexes have better potency when compared with pure drug.
Keywords: Bioassay; Complexation; Intrinsic dissolution; Norfloxacin; Beta-cyclodextrin